Ритм сезонного розвитку північноамериканських видів роду Rhododendron L. в умовах Львова - Tymchyshyn, H.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2013)
The paper contains the data on natural growing conditions of North-American Rhododendron L. taxa as well as climatic conditions in their cultivation area. The phenological rhythms of the rhododendrons of North-American origin as well as their flowering features and richness have been examined. High adaptive biorhythmical characteristics of the studied plants provide the reason to recommend them for planting in Western Ukraine.